ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (STUDI KASUS INDUSTRI RUMAHAN KEMPLANG DI WILAYAH JAKABARING PALEMBANG) - Jannati, Nur Sindi; Rusdi, M; Melis, Melis (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This study aims to determine and analyze the impact of the Covid-19 pandemic on the income of the cracker/kemplang home industry in the Jakabaring District, Palembang City. The analytical method used in this research is a qualitative method with data collection techniques in the form of interviews, discussions with business actors and from several sources of other articles. From the research that has been carried out, it is found that the cracker/kemplang home industry continues to run its business, and the income earned by the cracker/kemplang home industry tends to be stable even in the Covid-19 pandemic situation. The factor that supports the traders to keep doing business is the awareness to continue to struggle to meet the needs of their daily lives. There are several attempts by business actors to increase an income, such as by adapting to market changes, providing good service to consumers and paying attention to the quality of goods to be sold to consumers.